Frequency of Common Bile Duct Stones Detected on ERCP in Patients Presenting with Obstructive Jaundice & Having Normal CBD on Ultrasound Abdomen (Medical Forum Monthly, 2024)
Objective: To determine the frequency of Common stones in Bile Duct detected on Endoscopic Retrograde Cholangiopancreatography (ERCP) in patients presenting with obstructive jaundice & Having Normal CBD on ultrasound Abdomen.Study Design: Cross sectional study.Place and Duration of Study: This study was conducted at the department of Gastroenterology, Liaquat National Hospital, Karachi from July to December 2016.Materials and Methods: Total 162 patients with obstructive jaundice of 2-4 weeks duration and normal ultrasound abdomen were included. Before ERCP, patients were clinically evaluated. Outcome variable was the presence of CBD stone in ERCP. Descriptive statistics of the collected data were computed. Stratification was done. For post stratification, Chi-square test was applied. Confidence interval was kept to be 95% and the level of significance was kept to be 5%.Results: Number of male respondents was 106 and the female respondents were 56. Average age was 35.69±11.30 years. Mean duration of jaundice was 2.94±0.81 weeks. The CBD stone was 32.7% detected in ERCP. Significant association of age was observed with CBD stone in ERCP.Conclusion: ERCP is the gold-standard for the diagnosis and evaluation of morphological changes in the pancreas. In the common stones of bile duct, for treatment, ERCP is the preferred modality.